2020
DOI: 10.1155/2020/5217165
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Mechanism of Impact between Curved Bridge Segments Using Nonsmooth Dynamics

Abstract: It has been observed in many previous earthquakes that impact often occurs between the main girders in curved bridges. An earthquake can result in deck-unseating leading to catastrophic destruction of the structure. In this paper, the nonsmooth multirigid body dynamics method and the set-valued formulation were used to model and analyze the mechanism of impact between the curved bridge segments. The analysis demonstrated that these impacts are the major cause of segment rotation. The main contribution of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The near-fault pulse-type ground motion will increase the collision possibility and impact effect of the curved beam bridge. The impact of near-fault pulsed ground motions should be considered in the analysis of collision effects (Li et al, 2020). In this earthquake, a total of 16 sets of strong earthquake records were collected.…”
Section: Seismic Performance Of Girder Bridgementioning
confidence: 99%
“…The near-fault pulse-type ground motion will increase the collision possibility and impact effect of the curved beam bridge. The impact of near-fault pulsed ground motions should be considered in the analysis of collision effects (Li et al, 2020). In this earthquake, a total of 16 sets of strong earthquake records were collected.…”
Section: Seismic Performance Of Girder Bridgementioning
confidence: 99%
“…where K h is the pounding stiffness of the Hertz-damp model. The pounding stiffness is equal to the first-order modal stiffness of the bridge, which can be calculated based on previous studies [19,25]. δ m is the maximum intrusion displacement between the two contact surfaces.…”
Section: Pounding Parametersmentioning
confidence: 99%
“…They thought that the pounding significantly affected the bending moments of the piers and the transverse relative displacements between the deck and the abutment. Xu et al [25,26] studied the pounding effect and its influence on curved bridges with a small radius and a longitudinal slope subjected to near-fault ground motions. They found that pounding responses were significantly influenced by the characteristics of excitation, the peak pounding forces under bidirectional excitation were more significant, and the pounding force near the short pier was greater than that of the tall pier.…”
Section: Introductionmentioning
confidence: 99%
“…Shi and Dimitrakopoulos [32] assessed and compared the capacity of the non-smooth approach and force-based approaches to simulate the seismic response of a case study straight bridge. Additionally, Banerjee et al [33] and Li et al [34] calculated the complex dynamic behavior of pounding between a curved beam and an abutment or an adjacent beam. Banerjee et al [35] simulated the pounding between a curved beam and an abutment and investigated the ideal combination of the column and bent arrangement and the gap distance.…”
Section: Introductionmentioning
confidence: 99%